Pengaruh Adsorpsi Fe Dalam Air Asam Tambang Terhadap Luas Permukaan Adsorben - Mycelia Paradise, (ReTII, 2022)
Adsorption is one of the effective methods to reduce heavy metals in water. One of the important factors for the success of the adsorption process is the adsorbent. This research utilizeed clay, zeolite, and coconut shell activated charcoal as composites to absorb Fe. The adsorption process was carried out in a batch system with a composite mass of 2.5 grams, stirring speed of 300 rpm and contact time of 30 minutes. The results showed that the adsorbent had a surface area of ​​62.442 m2/g. After the adsorption, the surface area decreased to 56.050 m2/g. The decreasing of surface area of ​​the adsorbent was in line to the decreasing of Fe concentration after adsorption, from the initial concentration of 13.006 mg/L to 0.1484 mg/L. This indicated that the composite as an adsorbent has succeeded in absorbing Fe and the pores were filled with Fe and other heavy metals. Keywords: adsorption, adsorbent, Fe, surface area